Real-Time Railway Track Crack and Obstacle Detection System using Arduino and IoT Alert - Yukta P Gosavi; Aditi J Khalkar; Dipali A Jagatap; Kalyani Y Mahajan; Nitin D. Sonawane (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The safety and efficiency of railway operations rely heavily on the condition of the tracks. Cracks and obstacles on the tracks can lead to catastrophic consequences, including derailments and loss of life. This paper presents a real-time railway track crack and obstacle detection system using Arduino and IoT alert. The proposed system utilizes a combination of sensors, including ultrasonic and infrared sensors, to detect cracks and obstacles on the tracks. The sensor data is transmitted to an Arduino board, which processes the data and sends alerts to railway authorities via IoT protocols. The system is designed to provide real-time monitoring and alert capabilities, enabling prompt action to be taken to prevent accidents. The proposed system has been tested and validated, demonstrating its effectiveness in detecting cracks and obstacles on railway tracks.